Динаміка і міцність корпусів та опорних елементів конструкції гідрогенераторів - Кобзар, Ігор Володимирович; Полієнко, Владислав Русланович; Гнитько, Олександр Миколайович; Третяк, Олексій Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Виконано аналіз причин виникнення аварійних ситуацій в вузлі підп’ятника гідрогенератора великої потужності. Розглянуто існуючі методики розрахунків напруженого стану камер підп’ятника, як найбільш навантажених елементів гідроагрегату. Вивчено основні особливості роботи вузла підп’ятника стосовно до опор ковзання. Представлена оновлена схема навантаження опор ковзання. Вперше виконаний розрахунок пружних камер підп’ятника в тривимірній постановці з урахуванням фізичних властивостей масла, матеріалу камер і нерівномірності існуючих навантажень.

The basic designs of Hydrogenerators are considered in the presented scientific work. It is shown that one of the most loaded units of Hydrogenerator is the thrust bearing. The analysis of the causes of emergencies in the thrust bearing unit of the high power Hydrogenerator is performed based on the experience of operation. Cause-and-effect relations of origin and development of defects are determined. Existing methods of calculation of the stressed state of the chambers of the thrust bearing unit in the classical formulation for the stationary mode of operation are considered. The main features of the thrust bearing unit operation with respect to the features of the sliding supports were studied. An updated Diagram of the sliding supports loading is presented. For the first time, the calculation of the elastic chambers of the thrust bearing was performed in three-dimensional formulation taking into account the physical properties of the oil, the material of the chambers and the unevenness of the existing loads. It is shown that the applied designs of SE “Рlant “Electrotyazhmash” can be used in high power Hydrogenerators in the entire range of operational loads without restrictions.
Dynamics and strength of housings and supporting elements of hydrogenerator design
Keywords: підп'ятник; втомний розрахунок; тривимірне моделювання; крива втоми; the thrust bearing; fatigue calculation; three-dimensional modeling; fatigue curve